2022
DOI: 10.20937/atm.53042
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting Severity of Thunderstorm Associated with Strong Wind Flow Over Indian Subcontinent: Resource Lightning Surges

Abstract: Lightning Detection Systems (LDS) have a vital role in the real-time identification of the location of lightning strikes for the purpose of weather forecasting and issuing warning with sufficient lead time for safe operations. The spatial and temporal distribution of lightning, formulated using LDS observations, can be an objective input to infer and refine the climatology of Thunderstorm (TS) over a region. This study uses the data of Indian Air Forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Considering the lifetimes of meso-scale systems, this result is in line with expectations. It has been revealed in many studies in the literature that TS events mostly occur in the afternoon and evening hours (Karan, 2007;Kahraman et al, 2016;Pandit et al, 2023;Yavuz et al, 2022a). In this study, it was found that only 16% of the events occurred at night (0000-0600 UTC), and 61% of them occurred in the time period from sunrise to sunset.…”
Section: Frequency and Duration Of The Ts Eventsmentioning
confidence: 59%
See 1 more Smart Citation
“…Considering the lifetimes of meso-scale systems, this result is in line with expectations. It has been revealed in many studies in the literature that TS events mostly occur in the afternoon and evening hours (Karan, 2007;Kahraman et al, 2016;Pandit et al, 2023;Yavuz et al, 2022a). In this study, it was found that only 16% of the events occurred at night (0000-0600 UTC), and 61% of them occurred in the time period from sunrise to sunset.…”
Section: Frequency and Duration Of The Ts Eventsmentioning
confidence: 59%
“…To investigate these conditions, case studies and climatological analyzes have been carried out at various airports worldwide (Drozdov et al, 2013;Ryley et al, 2020;Taszarek et al, 2020;Yavuz et al, 2020). Pandit et al (2023) found that TSs at 12 airports in India occur mostly between at 1200-1400 UTC. This phenomenon is attributed to the atmospheric boundary layer being characterized by turbulent kinetic energy, turbulent momentum, sensible and latent heat fluxes, and vertical wind shear.…”
Section: Introductionmentioning
confidence: 99%